The dark and the bright side of liquidity risks: Evidence from open-end real estate funds in Germany - Fecht, Falko; Wedow, Michael (Journal of Financial Intermediation, 2014)
During the 6-month period from December 2005 to June 2006, the German Real Estate mutual fund industry suffered an unprecedented liquidity crisis. We investigate to what extend competing theories of liquidity crises help explain this event. Our results show that fundamental factors not only mattered for the liquidity outflow in normal times but also during the crisis. However, strategic complementarities accelerated the withdrawals during the crisis suggesting that pure panic behavior contributed substantially to the massive outflows. Thus higher liquidity buffers might help mitigating these tail events. Furthermore, we find that funds with a lower fraction of shares held by institutional investors suffered from less significant outflows suggesting that a segmentation of funds for different investor groups might help mitigate panics.